Terahertz Technology Fundamentals and Applications - Rostami, Ali.; Rasooli, Hassan; Baghban, Hamed; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"Terahertz Technology" presents information about Terahertz science, Terahertz photodetectors and Terahertz Lasers. A special emphasis is given to room temperature operation of long wavelength photodetectors based on novel quantum dots (Centered Defect Spherical Quantum Dots). Moreover, a complete analysis of systems based on Quantum Cascade structures to detect far infrared wavelengths is provided. Finally, the book presents Terahertz laser principles considering multi-color lasers in this range of wavelengths.
Keywords: Microwaves; Optical materials; Materials Science; Optical and Electronic Materials; Microwaves, RF and Optical Engineering; Optics, Optoelectronics, Plasmonics and Optical Devices